The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1097/dbp.0000000000000188
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Evaluation of the QTc Interval and Antidepressants in Youth

Abstract: The results suggest that most antidepressants are not associated with prolonged QTc at doses typically prescribed for children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
(14 reference statements)
1
5
0
1
Order By: Relevance
“…Further details about the i2b2 platform can be found in earlier analyses by this group. 10,11 This study was approved by the Partners Healthcare institutional review board with a waiver of the informed consent requirement because it utilized deidentified data only.…”
Section: Methodsmentioning
confidence: 99%
“…Further details about the i2b2 platform can be found in earlier analyses by this group. 10,11 This study was approved by the Partners Healthcare institutional review board with a waiver of the informed consent requirement because it utilized deidentified data only.…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that the patient's sertraline ingestion contributed to her QTc, but Takotsubo cardiomyopathy itself is associated with QTc prolongation and prior research has shown that sertraline causes minimal effects on the QTc interval compared with other selective serotonin reuptake inhibitors like citalopram. [21][22][23] Interestingly, the selective serotonin-norepinephrine reuptake inhibitor venlafaxine has been implicated in the development of Takotsubo cardiomyopathy. [24][25][26] In addition to blocking the reuptake of serotonin from the synaptic cleft, venlafaxine causes a pro-adrenergic state via norepinephrine reuptake inhibition that, based on the literature described, could cause Takotsubo cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…We used the Downs and Black quality checklist to assess the reporting, external validity, internal validity and statistical power of these nine studies ( S8 Table ). [ 54 ] Based on this checklist, the quality was rated as good for two studies [ 5 , 27 ], fair for five [ 14 , 23 , 26 , 28 29 ] and poor for two (never published). [ 19 , 20 ] Out of the published studies, three focused on QT prolongation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] These safety warnings have been controversial,[ 23 25 ] with inconsistent findings in other follow-up studies. [ 5 , 14 , 23 , 26 29 ] Many of these studies were limited by the use of QT prolongation rather than ventricular arrhythmia risk,[ 14 , 26 , 28 ] a young population cohort,[ 5 , 23 , 27 , 28 ] low statistical power,[ 26 ] and not accounting for important confounding factors in the analysis. [ 29 ] Escitalopram (the S enantiomer of citalopram) has also been associated with QT interval prolongation and Health Canada warns against the use of >10mg/day of escitalopram for patients 65 years of age or older.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation